2017
DOI: 10.1016/j.livres.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic progenitor cell activation in liver repair

Abstract: The liver possesses an extraordinary ability to regenerate after injury. Hepatocyte-driven liver regeneration is the default pathway in response to mild-to-moderate acute liver damage. When replication of mature hepatocytes is blocked, facultative hepatic progenitor cells (HPCs), also referred to as oval cells (OCs) in rodents, are activated. HPC/OCs have the ability to proliferate clonogenically and differentiate into several lineages including hepatocytes and bile ductal epithelia. This is a conserved liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 75 publications
1
35
0
1
Order By: Relevance
“…Previous studies have demonstrated that ductular reaction cells appear during chronic liver injury and differentiated into hepatocytes, thus maintaining hepatic homeostasis (Fellous et al 2009 ; Passman et al 2015 ; Bria et al 2017 ). In our study, we first confirmed that severe liver injury existed in human chronic liver injury (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that ductular reaction cells appear during chronic liver injury and differentiated into hepatocytes, thus maintaining hepatic homeostasis (Fellous et al 2009 ; Passman et al 2015 ; Bria et al 2017 ). In our study, we first confirmed that severe liver injury existed in human chronic liver injury (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The self-renewal capacity of mature hepatocytes contributes to adult liver homeostasis and regeneration; however, the nature of impaired regeneration resulting from chronic liver damage remains unclear (Forbes and Newsome 2016 ; Chien et al 2018 ; López-Luque and Fabregat 2018 ), and the capacity for self-renewal is overwhelmed following persistent chronic liver injury. In this condition, ductular reaction cells (known as HPCs) expressing SOX9 and cell keratin 19 (CK19) emerge, become activated and then differentiate into functional hepatocytes (Fellous et al 2009 ; Passman et al 2015 ; Bria et al 2017 ). However, the relative contribution of HPCs to parenchymal regeneration remains controversial (Michalopoulos and Khan 2015 ; Reid 2015 ; Kopp et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…38 Ductular reaction is commonly seen in liver diseases with chronic injury 63 and represents the expansion of DCs, also known as oval cells in rat and HPCs in some literatures. 63,64 Morphologically, DCs are small cells with a high nuclear/ cytosol ratio. Their origin is controversial and may represent different populations depending on the nature of injury.…”
Section: Role Of Hmgb1 In Ductular Reactionmentioning
confidence: 99%
“…They express several biliary cell markers, such as CK19, Sox9, and EpCAM, and hepatocyte markers, such as CK18 and albumin. 63,64 The driving force for the expansion of DCs is still far from clear. In autophagy-deficient livers, HMGB1 seems to be a major driving force.…”
Section: Role Of Hmgb1 In Ductular Reactionmentioning
confidence: 99%
See 1 more Smart Citation